KIDNEY FUNCTIONS IN ANEMIA IN PREGNANT WOMEN (World Bulletin of Public Health, 2024)
A normal pregnancy places great demands on a woman’s body. During pregnancy, big changes occur in the body. Every day, the developing fetus requires large energy expenditures from the mother’s body, which can be satisfied with enormous efforts from various body systems, including the hematopoietic organs. During pregnancy, the blood picture changes significantly. The total number of red blood cells and hemoglobin increases by an average of 18-20% ( A.A. Kadyrova , 1969; E.M. Feder , 1973). The need for vitamins, proteins, and microelements increases. Absorption of iron for the needs of the fetus and mother during pregnancy occurs 5-6 times faster. Anemia of pregnancy is quite common in obstetric practice and is one of the serious complications of pregnancy, childbirth and the postpartum period. Anemia in pregnant women is quite often combined with extragenital pathology, which in turn affects the frequency and amount of blood loss during childbirth according to data from pregnant women at different stages of pregnancy. The studies were conducted upon admission to the hospital, during treatment and before discharge from the hospital
Keywords: anemia; pregnancy; kidney disfunction; postpartum period